Recurrent Urinary Tract Infections (UTIs): A Review and Proposal for Clinicians - Dino Sgarabotto; Elena Andretta; Camilla Sgarabotto (Antibiotics)
The pathogenesis of recurrent urinary tract infections (rUTIs), a common problem in the female population, is becoming better understood following recent studies of bacterial persistence and intracellular bacterial communities. Incorporating these new insights, we propose pulsed antibiotic therapy with intracellular activity as a possible treatment for rUTIs.